How do you solve #5x^2 -6x +7 = 0# using the quadratic formula?

1 Answer
Sep 7, 2016

Answer:

#x = (3 - sqrt(26)) / 5, (3 + sqrt(26)) / (5)#

Explanation:

We have: #5 x^(2) - 6 x + 7 = 0#

Let's apply the quadratic formula:

#=> x = (- (- 6) pm sqrt((- 6)^(2) - 4 (5) (7))) / (2 (5))#

#=> x = (6 pm sqrt(36 - 140)) / (10)#

#=> x = (6 pm sqrt(- 104)) / (10)#

#=> x = (6 pm sqrt(104) i) / (10)#

#=> x = (6 pm 2 sqrt(26)) / (10)#

#=> x = (3 pm sqrt(26)) / 5#

Therefore, the solutions to the equation are #x = 3 - sqrt(26)# and #x = 3 + sqrt(26)#.